Spectroscopic Analyses of Oscillations in ECTO-NOX-Catalyzed Oxidation of NADH - D. James Morré; Dorothy M. Morré (SAGE Publishing, 2003)
Spectroscopic strategies that substantiate periodic oscillations in low rates of NADH oxidation exhibited by ECTO-NOX proteins at the animal and plant cell surface are described. Both continuous display and discontinuous rate determinations exhibit the oscillations but continuous displays lack sufficient resolution to discern details. A procedure is documented where rates are determined by least squares analyses of traces recorded over 1 min at intervals of 1.5 min. These traces recapitulate the continuous displays but offer an opportunity to reliably estimate changes in reaction rates over short time intervals not afforded by the continuous traces. Results from previously used rate determination over 5 min intervals are included for comparison. Turbidity is identified as the major contributor to losses in resolution. Even highly purified NOX preparations tend to aggregate to form turbid suspensions. With turbid suspensions, double beam or dual wavelength instrumentation where the sample is placed immediately adjacent to the photomultiplier tube are required to reduce losses in resolution from turbidity. Also required are high levels of synchronous ECTO-NOX function. Blue or red (plants) light, small molecules (i.e., melatonin) and autosynchrony alone or in combination were used to synchronize the oscillations. Special problems posed by preparations containing more than one ECTO-NOX form and where the different ECTO-NOX forms do not cross entrain are discussed.